STUDI LITERATUR : SOLUTION-FOCUSED BRIEFING COUNSELLING (SFBC) DALAM MENINGKATKAN INTERAKSI DAN KOMUNIKASI INDIVIDU - Dewika Putri Agustina (SHINE: JURNAL BIMBINGAN DAN KONSELING, 2024)
This research aims to study hypothetically the application of Solution-Focused Brief Counseling (SFBC) in families and several examples of solution-focused family counseling cases. The research method used is a literature review which uses various written sources such as journals and articles that are relevant to the study in this research. The focus of the research literature review is articles published in national journals regarding aspects of research titles, research methods and research results. The researcher chose a literature review because the researcher wanted to see a general overview of research on the application of Solution-Focused Brief Counseling (SFBC) in families and several case examples of solution-focused family counseling..